1996
DOI: 10.1159/000117214
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Relation between High Hemoglobin Values and the Risk of Ischemic Stroke

Abstract: We examined the relationship between the hemoglobin concentration and the risk of ischemic stroke using data from a hospital-based case-control study. A total of 143 patients (age 30-69 years) with a diagnosis of cerebral infarction confirmed by computerized tomography scan and 143 age- and sex-matched controls entered the study. Hemoglobin was higher in the patients with stroke (14.2 ± 1.6 g/l, mean ± SD) than in controls (13.7 ± 1.6 g/l; p< 0.05). Compared with subjects with hemoglobin levels of less than 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is in strong contrast to findings from the general population, in which high, not low, hemoglobin was associated with an increased risk (33)(34)(35)(36). However, these studies may have had insufficient power to detect an association between very low hemoglobin levels and stroke given the low prevalence of severe anemia in the non-ESRD population.…”
Section: Discussionmentioning
confidence: 58%
“…This is in strong contrast to findings from the general population, in which high, not low, hemoglobin was associated with an increased risk (33)(34)(35)(36). However, these studies may have had insufficient power to detect an association between very low hemoglobin levels and stroke given the low prevalence of severe anemia in the non-ESRD population.…”
Section: Discussionmentioning
confidence: 58%
“…One possible explanation was that the abnormally high hemoglobin concentration might lead to high blood viscosity and increased vascular occlusion, thereby causing retention of fat and total cholesterol within the cells and ultimately resulting in heart disease or stroke. 36 Because smoking and other blood parameters (eg, mean corpuscular volume and mean corpuscular hemoglobin concentration) were not available in our study, we were unable to make specific interpretations regarding the observed relationship between hemoglobin level and risk of MS. But our finding may further support the modified criteria of MS that identify population at high risk for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 93%
“…It is unclear whether the increase in red blood cells and hemoglobin is beneficial. Elevated hemoglobin is associated with an increased risk of ischemic stroke and increased red blood cell counts may be a predictor of acute cardiovascular events .…”
Section: Discussionmentioning
confidence: 99%